Digital marketing for dummies - Deiss, Ryan; Henneberry, Russ (For dummies, 2017)
Written with the marketer's best interests in mind, this friendly, down-to-earth guide shows you how to use proven digital marketing strategies and tactics to expand the reach of your brand, increase audience engagement, and acquire and monetize customers. --